PjBL Strategy on the Motivation of Students' Learning Interest in Fiqh Learning at Madrasah Ibtidaiyah Al-Hidayah Lumbang Probolinggo - Bani, Rahmat; Soliha, Imro Atus (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This study investigates the effectiveness of Project-Based Learning (PjBL) strategies in enhancing students' interest and active participation in Fiqh education at MI Al-Hidayah. Many students at MI face significant challenges in mastering Fiqh, resulting in low levels of engagement during lessons. Suboptimal academic performance in this subject is often attributed to the reliance on ineffective instructional methods. Consequently, the integration of PjBL emerges as a critical strategy for enriching learning experiences and promoting practical application within the educational framework of MI. Adopting a qualitative methodology through a case study design, the research collected data using in-depth interviews to gain comprehensive insights. Additionally, both participatory and non-participatory observations were employed to capture authentic behaviors within natural contexts. These methods were further supplemented by the triangulation of data from multiple relevant sources. The findings reveal that PjBL has a significant positive impact on the quality of Fiqh education at MI Al-Hidayah. This pedagogical approach not only increases student engagement and interaction but also enhances their understanding of fundamental concepts. Moreover, PjBL fosters the development of critical social skills, such as collaboration, an appreciation for peaceful coexistence, and a heightened sense of responsibility. These outcomes contribute to the holistic development of students, aligning with the broader educational objectives of MI